The Effectiveness of Behavior Modification-Based Group Counseling Using Social Skills Training Techniques to Prevent Phubbing Among Online Gamers - Tarmuzi, M. Fadlan Choiri; Nurfarhanah, Nurfarhanah; Ardi, Zadrian; Handayani, Puji Gusri (Grief and Trauma, 2026)
This study aims to examine the effectiveness of group counseling services based on behavior modification using social skills training techniques in preventing phubbing behavior among students who play online games. This study employed a quasi-experimental design with a pretest–posttest control group. The study sample consisted of 20 students divided into experimental and control groups. Data were collected using a phubbing scale and analyzed using the Wilcoxon Signed Ranks Test and the Mann–Whitney U Test. The results showed a significant decrease in phubbing behavior in the experimental group (p < 0.05), with the average score decreasing from 103.7 to 73.2 (Δ = 30.5), while in the control group, the decrease was from 91.6 to 79.4 (Δ = 12.2). The decrease in the experimental group was greater and more consistent compared to the control group. These findings indicate that group counseling services based on behavior modification using social skills training techniques are effective in improving social skills and reducing smartphone dependence in social interactions.